Labour force in the tea plantation sector: a special reference to privatized large scale tea estates in sri lanka - Chandrabose, A.S. (University of Jaffna, 2012)
Technically tea plantation is a labour intensive sector and it requires 2.5 labours per hectare. However, the privatized tea plantation could not retain land labour ratio. The land for extension of tea remains unchanged, however, the number of registered workers have been declined by 42% from 405,304 in 1990 to 242,266 in 2010. The focus of this study is to find out the reasons for the drop and to analyse the strategy adopted by both the workers and the estate management in order to rectify the situation. The study found diversity of employment among the tea workers. As literacy provides extra avenues for alternative jobs, mobility from tea estate works to non-estate works increases. The privatized tea estate is engaging in recruitment of temporary workers mainly from the non-traditional tea sector rather than resident workers.